Carbon microsphere encapsulated SnS for use as an anode material in full‐cell sodium‐ion battery. (15th November 2021) - Islam, Mobinul; Ali, Basit; Jeong, Min‐Gi; Akbar, Muhammad; Chung, Kyung Yoon; Nam, Kyung‐Wan; Jung, Hun‐Gi
Summary: Tin(II) sulfide (SnS) has long been regarded as an attractive anode material for sodium‐ion batteries (SIBs). However, structural pulverization and severe volume expansion result in a poor cycle life for SnS, making its use in practical battery systems difficult. To address these issues, we propose a surfactant‐assisted one‐pot hydrothermal approach for successfully encapsulating in situ formed SnS particles in a micro‐carbon sphere (MCS). The morphology and the electrochemical behavior of the products were investigated by varying the controlling parameters, such as the concentration of surfactants, polyvinylpyrrolidone (PVP), and cetyltrimethylammonium bromide (CTAB), as well as the concentration of SnS precursors in the reaction system. When used as an anode material for SIBs, the MCS embedded SnS electrode delivered a reversible specific capacity of 465 mAhg −1 at 0.1 Ag −1 and retained a reversible capacity of 371 mAhg −1 at 0.5 Ag −1 after 250 cycles. Moreover, the SnS@MCS electrode maintained specific capacities of approximately 256, 206, and 160 mAhg −1 at very high specific current densities of 5, 10, and 20 Ag −1, respectively. Certainly, the carbon matrix served as a cushion to absorb volume expansion and facilitate the movement of the Na + ions and the electrons within the electrode. Consequently, a honeycomb‐structured Na3 Ni2 SbO6 cathode was synthesized using a solid‐state approach to evaluate the feasibility of the SnS@MCS anode in a full‐cell configuration. The full‐cell operated at an average voltage of 3.25 V, with a specific capacity of 80 mAhg −1, and demonstrated a specific energy density of ≈266.7 Whkg −1 . This work could serve as a research guide for the future investigation of alloy and conversion‐based anode materials in SIBs. Abstract : In situ formation of SnS particles encapsulated in a micro‐carbon sphere, which buffers the severe volume variations during prolonged electrochemical cycling, as a high‐performance anode material for sodium‐ion batteries.